Carbon conversion by Methanococcus maripaludis S2 under diazotrophy and a revised genome-scale metabolic model - Vo, Chi Hung (2023)
Methanococcus maripaludis can utilize CO2 as the sole carbon source. Since N2 is a major component of most flue gases, understanding its impact on the cellular behaviours of M. maripaludis is critical. Here, we studied CO2 conversion by M. maripaludis S2 in minimal media with ammonium or N2 as the sole nitrogen source. N2-grown cultures exhibited a long lag phase, prolonged growth phase, and lower cell density compared to ammonium. At any specific growth rate, the CO2 intake and CH4 evolution fluxes were higher for N2 than ammonium, suggesting that N2 is a better nitrogen source for carbon conversion to CH4. The flux measurements were used to improve a genome-scale metabolic model existing in the literature. The revised model iMR557 has a coverage of 32% open reading frames and includes new pathways. iMR557 was used to illustrate flux distributions under different conditions and successfully replicate the previously reported acetate dissimilation.